2006
DOI: 10.7326/0003-4819-145-6-200609190-00003
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death among Persons with AIDS in the Era of Highly Active Antiretroviral Therapy: New York City

Abstract: Non-HIV-related causes of death account for one fourth of all deaths of persons with AIDS. Cardiovascular disease, non-AIDS-defining cancer, and substance abuse account for most non-HIV-related deaths. Reducing deaths from these causes requires a shift in the health care model for persons with AIDS from a primary focus on managing HIV infection to providing care that addresses all aspects of physical and mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
263
1
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 398 publications
(294 citation statements)
references
References 36 publications
23
263
1
7
Order By: Relevance
“…These results agree with findings by other authors showing an increase in deaths from cardiovascular diseases in persons with HIV/AIDS since the introduction of HAART 13,16,17 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results agree with findings by other authors showing an increase in deaths from cardiovascular diseases in persons with HIV/AIDS since the introduction of HAART 13,16,17 .…”
Section: Discussionsupporting
confidence: 93%
“…Compared to 1999, the number of deaths listing non-AIDSrelated causes increased more in the group that listed HIV/AIDS on the death certificate when compared to the group not listing HIV/AIDS. Other authors have reported similar results for some time in developed countries 11,12,13,14,15 .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…A study realized by SACKOFF et al, of patients registered in New York City, showed an increased rate of mortality for causes related to HIV with advanced age (greater than 65 years) and in women 28 .…”
Section: Discussionmentioning
confidence: 98%